The intragraft microenvironment as a central determinant of chronic rejection or local immunoregulation/tolerance. Issue 1 (February 2017) - Wedel, Johannes; Nakayama, Hironao; Kochupurakkal, Nora M.; Koch, Josephine; Klagsbrun, Michael; Bielenberg, Diane R.; Briscoe, David M.
Abstract : Purpose of review: Chronic rejection is associated with persistent mononuclear cell recruitment, endothelial activation and proliferation, local tissue hypoxia and related biology that enhance effector immune responses. In contrast, the tumor microenvironment elicits signals/factors that inhibit effector T cell responses and rather promote immunoregulation locally within the tissue itself. The identification of immunoregulatory check points and/or secreted factors that are deficient within allografts is of great importance in the understanding and prevention of chronic rejection. Recent findings: The relative deficiency of immunomodulatory molecules (cell surface and secreted) on microvascular endothelial cells within the intragraft microenvironment, is of functional importance in shaping the phenotype of rejection. These regulatory molecules include coinhibitory and/or intracellular regulatory signals/factors that enhance local activation of T regulatory cells. For example, semaphorins may interact with endothelial cells and CD4 + T cells to promote local tolerance. Additionally, metabolites and electrolytes within the allograft microenvironment may regulate local effector and regulatory cell responses. Summary: Multiple factors within allografts shape the microenvironment either towards local immunoregulation or proinflammation. Promoting the expression of intragraft cell surface or secreted molecules that support immunoregulation will be critical for long-term graft survival and/or alloimmune tolerance.